The connexin 37 (1019C>T) gene polymorphism is associated with subclinical atherosclerosis in women with type 1 and 2 diabetes and in women with central obesity - Piťha, J; Hubáček, J A; Piťhová, P (Physiological research, 2010)
The gene for connexin 37 (Cx37) is considered to be one of the candidate genes for cardiovascular disease. We evaluated the association between Cx37 (1019C>T) gene polymorphism (Pro319Ser) and ankle brachial blood pressure index (ABI) in women with type 1 (n=178) and type 2 (n=111) diabetes, and in women from general population (n=862). All women were genotyped for Cx37 polymorphism. In addition to traditional cardiovascular risk factors, ABI was analyzed. In women with type 1 diabetes, ABI significantly decreased from TT to CC carriers (p for trend = 0.008). A similar trend was seen in women with type 2 diabetes (p = 0.050) and in women with waist circumference above 75th percentile (94 cm; n=208) of the general population (p = 0.049). The gene for Cx37 was associated with subclinical atherosclerosis in women with type 1 and 2 diabetes and in women with advanced central obesity. The presence of C allele indicated increased risk.
Keywords: diabetes mellitus 1. typu; konexiny; Connexins; Risk Factors; Gap Junction alpha-4 Protein; Genotype; polymorfismus genetický; protein alfa 4 mezerového spoje; ateroskleróza; Diabetes Mellitus, Type 2; Polymorphism, Genetic; diabetes mellitus 2. typu; Obesity, Abdominal; lidé; ženské pohlaví; Atherosclerosis; Humans; rizikové faktory; abdominální obezita; genotyp; Diabetes Mellitus, Type 1; Female; lidé středního věku; Middle Aged